Perancangan Sistem Informasi Penerimaan Peserta Didik Baru Dan Ujian Online Dengan Php Dan Codeigniter Di Smk Negeri 1 Sigli - Imilda; Suryadi, Oka; Ahmad, Lukman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Information system development is crucial in improving the efficiency and accuracy of the operational processes of an educational institution. In the context of SMK Negeri 1 Sigli, the problem of manual data management in the process of accepting new students requires an adequate solution. This research aims to design and implement a web-based information system for accepting new students and online exams at SMK Negeri 1 Sigli, using PHP and Codeigniter as the main programming languages. The research methods used include field studies, UML analysis, and various data collection techniques. It is hoped that the resulting information system can increase the efficiency of the process of accepting new students, provide better accessibility, and increase data accuracy.